Sahtu Wildlife Health Outreach and Monitoring Program: Evaluating the health of moose, barren-ground and mountain caribou in the Sahtu Region, Northwest Territories - Kutz, S.; Veitch, A. (Polar Data Catalogue, 2015)
We trained local wildlife health monitors (WHMs) to collect samples and record health and condition data on animals that they harvested for subsistence. A pilot project was developed in 2004 in Déline. Two aboriginal hunters that were recommended by the local Renewable Resource Council were trained by a wildlife veterinarian in sample collection techniques and data recording using a caribou that they had harvested. Hunters were given an information binder that described the purpose of the program and collection kits which consisted of a field clipboard with data sheets, sampling diagrams and a pencil and a ruler, and pre-labelled sample collection bags and tags. The WHMs were financially compensated for each set of samples and each annual training and update session that they attended. The program was expanded in 2005 to include four additional hunters from Colville Lake (barren-ground caribou) and Fort Good Hope (moose and boreal woodland caribou) and was continued through 2009. Samples obtained include jaw, metatarsal, blood on filter paper, feces, kidney, liver, and measures of back fat thickness.